Effect of Press Freedom on Sudanese Newspapers Framing of Corruption Issues - Hamid, Yassin Bashir; Mohammed, Assoc. Prof. Dr. Rosli; Ahmad, Dr. Mohd. Khairie (Jurnal The Messenger, 2019)
This research aims at exploring the effect of the press freedom on the newspapers framing of the issue of corruption in Sudan. A qualitative method was adopted using in-depth interviews to adequately explore the perspectives of the Sudanese journalists and editors towards the press freedom effect on the Sudanese newspapers in terms of framing the issues of corruption. A purposeful sampling was employed in selecting 20 Sudanese journalists and editors across both the governmental and private newspapers. Therefore, the study has significantly contributed to the overall perspectives of how newspapers framing affects public awareness about corruption and possible remedies in Sudan. The findings revealed that the legislation is significant in developing the press industry which has a great role in addressing the issues of corruptions.